2018
DOI: 10.14260/jemds/2018/225
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Patient Waiting and Consultation Time in the Outpatient Department at a Selected Tertiary Care Teaching Hospital

Abstract: BACKGROUND Outpatient department has become an essential part of the hospital due to the fact that it is the first step of the treatment system and point of contact between a hospital and community. Waiting time refers to the time a patient waits in the clinic being seen by one of the clinical medical staff. Objectives-1. To calculate the patient waiting and consultation time for each specialty. 2. To analyse the cause and effect for the delay. 3. To recommend appropriate suggestions to optimize the waiting ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The transition from paper to electronic medical records had a significant and positive impact on reducing long waiting time at the OPD. Various studies underlined the benefits of electronic medical records over paper-based systems, including how it can improve patient waiting time, increase efficiency, and improve the delivery of healthcare services [ 10 , 11 ] and [ 12 ]. Another study highlighted the preference for electronic health records among healthcare providers due to their efficiency and speed in patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from paper to electronic medical records had a significant and positive impact on reducing long waiting time at the OPD. Various studies underlined the benefits of electronic medical records over paper-based systems, including how it can improve patient waiting time, increase efficiency, and improve the delivery of healthcare services [ 10 , 11 ] and [ 12 ]. Another study highlighted the preference for electronic health records among healthcare providers due to their efficiency and speed in patient care.…”
Section: Discussionmentioning
confidence: 99%
“…A tertiary medical college hospital in Mangalore, Karnataka, evaluated patient waiting and identified disorganized manual files as a primary cause of delays. These findings underscore the disadvantages of paper-based records and suggest that implementing electronic medical records (EMRs) can greatly enhance efficiency [ 11 ]. Reducing outpatient waiting times is a critical challenge for healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
“…The first paper found that the average waiting time for patients is 41 minutes and the average consultation time is 18.21 minutes, resulting in a total of 59.21 minutes for the patient's journey (Ahmad, Khairatul and Farnaza, 2017). The second paper found that the average waiting time is 44.85 minutes and the average consultation time is 17.36 minutes, amounting to a total of 62.21 minutes for the patient's journey (Thapa et al, 2018).…”
Section: Consultation Timementioning
confidence: 99%
“…Authors of a systematic review concluded that the construct of healthcare satisfaction should be measured using a multidimensional approach, with the physical environment, patient–doctor communication, and hospital management processes serving as the primary domains of many instruments [ 18 ]. Overall satisfaction in hospitals is largely determined by outpatient satisfaction [ 19 , 20 ], which could be improved by effective patient–doctor communication [ 20 , 21 ], decreased medical costs, convenient medical treatment process and hospital environment, and shortened waiting time for medical services [ 22 , 23 , 24 , 25 ]. Whether mHealth can improve satisfaction levels is not well understood.…”
Section: Introductionmentioning
confidence: 99%